Nacionalização da política de assistência social e governos estaduais no Brasil: o caso do estado de São Paulo - Gomes, Maria do Rosario Corrêa de Salles (2008)
It is in course the elaboration of a new federative pact of Social Assistance Politic management, given by the implantation process of Social Assistance Unique System (SUAS). It means a no-contributive public system, decentralized and participative that give effectiveness to Social Assistance National Politic a closely bound division of responsibility between the federate beings, in a shared way of management, of co-financing and technical cooperation. Under the load of a process of political-administrative decentralization emphasized during the last 20 years of city council is made a need of a practical exercise re-definition of competences and responsibilities of each governmental scope. A first hypothesis suggest that the implementation of public social assistance decentralizing (therefore after 1988) is happening , primordially under a higher municipal and federal scope protagonist, beside a more dubious and secondary state scope protagonist. In such case, is needed a consideration of the influence of previous politics legacy for the actual proposition of a national politic of no-contributive social protection, that has not a republican tradition of social assistance partaken management. In such case, the institutional appearance of social assistance as state responsibility is presented, alongside the history, under different rhythms and times to the federate people. It s interesting to recognize the way how was shaped in the Brazilian states the responsibility about social assistance, which historic presence in Brazilian federation possess a political force that antecede the municipal presence in the federative pact. To refine the definition of the particular state responsibility management of an unified scheme undergo the knowledge of historic conditionings that determinate the management organs actual conformation, as well as the resistance and facilities to join a new federative pact required by SUAS. In such sense, the particular examination of eight states permit to detect similarities and differences among themselves, approximation of federal scope influence over the state and regional order particularities